RESISTENSI AZOTOBACTER TERHADAP MERKURI DAN PENGARUHNYA PADA PERTUMBUHAN JAGUNG (ZEA MAYS L.) DI TAILING TAMBANG EMAS - Hindersah, Reginawanti; Adawiah, Aliya Zahrah; Suryatmana, Pujawati; Dewi, Triyani (Jurnal Teknologi Mineral dan Batubara, 2024)
Rhizobacteria from the N-fixing Azotobacter genera can be used as bioremediation agents. Azotobacter produces exopolysaccharides (EPS) that chelate heavy metals and synthesize metabolites to promote plant growth. This research aimed to analyze the resistance of the Azotobacter consortium isolated from tailings contaminated with mercury (Hg) in synthesizing secondary metabolites in liquid cultures contaminated with Hg, as well as the effect of the Azotobacter consortium on corn growth in various tailings-based media compositions containing Hg. The Hg resistance test was carried out using a completely randomized design with 100, 200, and 400 mg/L HgCl2 in N-free media. The greenhouse experiment was designed in a randomized block design to treat various concentrations of organic matter in the tailings. The results showed that Azotobacter isolates were able to survive in Ashby broth containing Hg up to 400 mg/L, and the consortium produced significant amounts of auxin, gibberellin, cytokinin, oxalic acid, citric acid, and EPS. In addition, Azotobacter increased corn growth in Hg-contaminated tailings with the addition of 6:4 compost (tailings: compost). Azotobacter is resistant to Hg up to 400 mg/L; as a consortium, it can produce secondary metabolites and has a good influence on the growth of corn in tailings containing Hg.